User perceptions about sharing exposure notification information for communicable diseases - Schooley, Benjamin; Feldman, Sue S. (Frontiers in Digital Health, 2022)
The [app name blinded review] Exposure Notification System (ENS) was built and deployed in [state blinded for review] for anonymous sending and receiving of COVID-19 exposure alerts to people who have been in close contact with someone who later reports a positive COVID-19 test. Little is known about how demographic groups perceive recent privacy preserving ENS innovations including their usability, usefulness, satisfactions and continued interest in sharing COVID-19 exposure information. The purpose of this study was to investigate how users across demographic groups perceive the sharing of exposure information with various types of organizations and to investigate how end user perceptions of ENS usability, usefulness, and satisfaction differ across demographic groups within the context of a statewide deployment of an exposure notification system. Methods A survey was administered to [state residents blinded for review] (N=1049) to assess propensity to share COVID-19 infection data and evaluate end user perceptions about usability, usefulness, and satisfaction with the [state blinded for review] ENS. ANOVA and Tukey Honestly Significant Difference (HSD) post hoc tests were conducted to assess demographic group differences. Results ENS survey participants had a high awareness of contact tracing, exposure notifications, and the [app name blinded for review] ENS, and reported having downloaded the app. Survey results revealed the majority of participants rated the app as useful (n=490, 79%), easy to use (n=490, 79%), and reported satisfaction with its use (n=546, 88%). Other results suggest that ethnicity and age may be important factors for trust in sharing exposure information. Conclusions The [app name blinded for review] system was one integrated component of a comprehensive education and work re-entry strategy across [state blinded for review] that reached a broad user base. Users across different demographic groups perceive the sharing of information about their communicable disease exposures differently. Further, demographic factors play a role in which types of organizations individuals are willing to share their communicable disease exposure information. Public health institutions, employers, schools, healthcare providers and technology designers may want to consider these findings as they construct technologies and perform outreach campaigns aimed at reducing infection rates with ENS and related technologies.